Diary, 1853 - Town, Clarissa E. Leavitt (Plantation records ;, 1973)
Typescript of "Grandma Town's Diary" prepared by her great-granddaughter, Josephine R. Devall of Prairieville, Louisiana, 1954. Entries, January-July, 1853, by Clarissa Town, native of Buffalo, New York, describe her life while living in the home of her daughter and her son-in-law, the Reverend A.H. Lamon, Protestant Episcopal clergyman in Devall, West Baton Rouge Parish. Entries pertain to trips to New Orleans and Baton Rouge, religious and social life among the slaves, and holiday celebrations. Among the prominent people mentioned in the diary are Leonidas Polk, Edward George Washington Butler, William Markham, and Louis Agassiz. Included is a photostatic copy of a section of the Persac map, 1858.